Damage Evolution Analysis of Rock Slope in Tunnel Entrance Section Under the Seismic Action. Issue 4 (September 2019) - Zhao, Jie; Lan, Wenjun; Wang, Guixuan; Zhang, Kai
Abstract: Starting from the microscopic heterogeneity feature of the rock material, the paper applies the theory of continuous medium damage mechanics and deduces the constitutive relation for microscopic damage of rock material. Afterwards, this paper sets ANSYS development platform as its main body and puts forward the equivalent damage unit based on the assumption of macroscopic homogeneity to simulate the damage cracking process of the rock side slope at the tunnel portal section based on the principle of microscopic damage mechanics. It is shown in the calculation results that the side slope damage and destruction involve a continuous damaging process from the microscopic perspective. Under the impact of seismic load, there will initially be micro cracks on the side slope structure. As time goes by, these micro cracks will gradually expand into larger ones and finally form penetrated damage area; especially, there will be penetrated damage area formed above the tunnel vault, which can be deemed as that the vault has been completely damaged and poses a negative influence on the safe operation of the tunnel. Therefore, the vault top should be reinforced during design and construction, and the calculation method and analysis results of this paper can be applied to the analysis of damage destruction in similar complex structures.